A Rising Tide Lifts All Boats: The Effects of Common Ownership on Corporate Social Responsibility - DesJardine, Mark R.; Grewal, Jody; Viswanathan, Kala (Organization Science, 2023)
Common owners face an incredible investment challenge: managing systematic risk. Because common owners hold shares in multiple firms across an industry, an action (or inaction) by one firm that affects industry peers is felt more severely by common owners than by non-common owners. Research has largely focused on common owners’ role in orchestrating competitive dynamics among their portfolio firms, with almost no empirical investigation of how common owners manage systematic risk. Drawing on research showing that one firm’s corporate social responsibility (CSR) can produce positive spillovers for peer firms and that its irresponsibility can harm its peers, we argue that common owners increase firms’ CSR to produce spillovers that reduce systematic risk and multiply their investment returns. Consistent with our theory, we find that common ownership is positively associated with firm CSR. Unpacking that relationship, we find that increases in CSR are driven by common owners with long-term orientations and are concentrated in stakeholder sensitive industries, in which CSR spillovers are most economically impactful. We also find that common owners focus their efforts on financially material CSR over financially immaterial CSR. We use a natural experiment with a quasi-exogenous shock to rule out alternative explanations. Our study contributes to literatures on the antecedents of CSR and outcomes of common ownership, providing a new perspective on how common owners shape corporate strategic behavior. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2022.1620 .